Alpha particle detector based on micro pixel avalanche photodiodes - Ahmadov, F.; Abdinov, O.; Ahmadov, G.; Anfimov, N.; Garibov, A.; Guliyev, E.; Krumshtein, Z.; Madatov, R.; Olshevski, A.; Shvetsov, V.; Sadigov, A.; Sadygov, Z.; et al. (Functional Materials, 2013)
The main goal of this work is a study of possibility to detect alpha particles by micro-pixel avalanche photodiode (MAPD) which has very thin active volume (4 μ m) and by micro-pixel avalanche photodiode in combination with Lutetium Fine Silicate (LFS) scintillators (500 μ m thickness). The obtained results show that alpha detectors based on MAPD are expected to be useful in many applications: public security (Associated Particle Imaging for explosives and drugs detection), radioactive contamination monitoring in various environments and detection of charged particles from nuclear reactions.